Prospective Evaluation of the Correlation Between Gated Cardiac Computed Tomography Detected Vascular Fibrosis and Ease of Transvenous Lead Extraction. (28th October 2022) - Patel, Divyang; Vatterott, Pierce; Piccini, Jonathan; Epstein, Laurence M.; Hakmi, Samer; Syed, Imran; Koweek, Lynne M.; Bolen, Michael; Schoenhagen, Paul; Tarakji, Khaldoun G.; Francis, Nathan; Shao, Mingyuan; et al.
Abstract : Background: Difficulty of lead extraction does not track well with procedural complications, but several small retrospective studies have lead fibrosis on computed tomography as an important indicator of difficult lead extraction. The purpose of the present study was to apply a standardized gated cardiac computed tomography (CT) protocol to assess fibrosis and study it prospectively to examine the need for powered sheaths and risk outcomes. Methods: We performed a prospective, blinded, multicenter, international study at high-volume lead extraction centers and included patients referred for transvenous lead extraction with at least one lead with a dwell time >1 year and ability to receive a cardiac CT. The degree of fibrosis (as measured by amount of lead adherence to vessel wall) was graded on a scale of 1 to 4 by dedicated CT readers in 3 zones (vein entry to superior vena cava, superior vena cava, and right atrium to lead tip). The primary outcome of the study was number of extractions requiring powered sheaths at zone 2 for each fibrosis group. Results: A total of 200 patients were enrolled in the trial with 196 completing full gated CT and lead extraction analysis. The primary endpoint of powered sheath (laser and mechanical) sheath use was significantly higher in patients with higher fibrosis seen on CT (scores 3+4; 67.8%) at the zone 2 compared to patients with lower fibrosis (scores 1+2; 38.6%; P <0.001). There were 5 major complications with 3 vascular lacerations all occurring in zone 2 in the study. Conclusions: Gated, contrasted CT can predict the need for powered sheaths by identification of fibrosis but did not identify an absolute low-risk cohort who would not need powered sheaths. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03772704.